AL QAEDA’S RADICAL IDEOLOGY - Ararat Kostanian (Jurnal Politik indonesia (Indonesian Journal of Politics), 2021)
The purpose of the essay is to illustrate the Ideological aspect of al Qaeda that constitutes the pillar of the organisation based on distinct interpretation of Quran and biased understanding of the meaning of Jihad. The functional method of al Qaeda is not simplistic or unsystematic, aimed at particular target or focused or specific country or region. The creation of such transnational organisation couldn’t have been revealed without political Ideology with its manifesto and the mechanism to spread its messages all over the world. It will not be correct to put al Qaeda among the category of the classical terror groups as I have shown in the essay as a comparison. Moreover, it is not similar to any categories of political Islam movements; since the distinction between Jihad and waging war has always been differentiated in the context of Political Islam. Whereas al Qaeda declares enemies in the house of Islam as well to countries, people and Institutions differ with their own created ideology. This distorted ideology has spread all over the world and become an enemy to Islam itself, which harmed the reputation of Islam as a religion. Attention on the ideologic context of al Qaeda hasn’t been researched well, unknown to majority of the experts. Instead, the attention at most has been put on its ground actions, security concerns and counter terrorism.